The role of the novel Th17 cytokine IL-26 in intestinal inflammation. Issue 9 (15th May 2008) - Dambacher, J; Beigel, F; Zitzmann, K; De Toni, E N; Göke, B; Diepolder, H M; Auernhammer, C J; Brand, S
Abstract : Background and aims: Interleukin 26 (IL-26), a novel IL-10-like cytokine without a murine homologue, is expressed in T helper 1 (Th1) and Th17 cells. Currently, its function in human disease is completely unknown. The aim of this study was to analyse its role in intestinal inflammation. Methods: Expression studies were performed by reverse transcription-PCR (RT-PCR), quantitative PCR, western blot and immunohistochemistry. Signal transduction was analysed by western blot experiments and ELISA. Cell proliferation was measured by MTS (3-(4, 5-dimethylthiazol-2-yl)-5-(carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) assay. IL-26 serum levels were determined by an immunoluminometric assay (ILMA). Results: All examined intestinal epithelial cell (IEC) lines express both IL-26 receptor subunits IL-20R1 and IL-10R2. IL-26 activates extracellular signal-related kinase (ERK)-1/2 and stress-activated protein kinase/c-Jun N-terminal kinase (SAPK/JNK) mitogen-activated protein (MAP) kinases, Akt and signal transducers and activators of transcription (STAT) 1/3. IL-26 stimulation increases the mRNA expression of proinflammatory cytokines but decreases cell proliferation. In inflamed colonic lesions of patients with Crohn's disease, an elevated IL-26 mRNA expression was found that correlated highly with the IL-8 and IL-22 expression. Immunohistochemical analysis demonstrated IL-26 protein expression in colonic T cells including Th17 cells expressing the orphan nuclear receptor RORγt, with an increased number of colonic IL-26-expressing cells in active Crohn's disease. Conclusion: Intestinal cells express the functional IL-26 receptor complex. IL-26 modulates IEC proliferation and proinflammatory gene expression and its expression is upregulated in active Crohn's disease, indicating a role for this cytokine system in the innate host cell response during intestinal inflammation. For the first time, IL-26 expression is demonstrated in colonic RORγt-expressing Th17 cells in situ, supporting a role for this cell type in the pathogenesis of Crohn's disease.